Kansei Engineering Approach for Measuring Political Propaganda: A Case of Malaysia - Saad, NurJannatul Jannah Aqilah Md; Afiza, Mat Razali Noor; Wook, Muslihah; Ishak, Khairul Khalil; Hamid, Hasmeda Erna Che; Hasbullah, Nor Asiakin; Wahab, Norshahriah; Zainudin, Norulzahrah Mohd; Ramli, Suzaimah; Amran, Mohd Fahmi Mohamad (International Journal of Engineering and Technology, 2018)
Propaganda is mainly designed to influence people’s mental state on new ideas which is crucially used for political agenda. Back in 1950s, people used mass media to propagate propaganda. Nowadays, the usage of social media as a tool for political propaganda agenda either by the politician or the supporters are creating a game diverge in electoral campaign. This phenomenon is occurring in all over the world including Malaysia. Studies has proven that people who rich in Kansei is rich in emotions and sentiment, adaptive, warm and responsive. Unfortunately, little effort has been paid to use the approach for measuring Malaysians’ emotions on political propaganda in various social media platforms. This study is proposing that Kansei Engineering (KE) could be used as an approach for analysing their emotion and sentiment. For this reason, KE incorporating with partial least squares (PLS) is used to measure and analyse the level of Malaysians’ emotions regarding political propaganda via social media by constructing emotional descriptor or KW by adapting PANAS-X. The proposed technique could be used as a basis to build a framework to hinder the diffusion of negative political propaganda in the social media settings particularly in Malaysia.